A novel spherical fuzzy AHP-integrated spherical WASPAS methodology for petrol station location selection problem: a real case study for Istanbul - Ayyildiz, Ertugrul; Taskin Gumus, Alev (SPRINGER HEIDELBERG, 2020)
The petrol station location selection problem is taken into consideration in this study. In order to identify the main and sub-criteria for evaluation, the literature is reviewed and five experts from different companies are interviewed. After that, thirteen different alternative locations are for specified to evaluation. Then, the novel spherical fuzzy AHP-integrated spherical WASPAS methodology is structured in a fuzzy environment, and the petrol station location selection problem is evaluated with this methodology. In this study, a real application is presented for Istanbul to show the applicability of the proposed methodology. Subsequently, a sensitivity analysis is performed to explain and analyze the proposed methodology results. Finally, the results are presented and discussed with future directions.
Keywords: Location selection; Petrol station; Spherical fuzzy; AHP; WASPAS; NETWORK PROCESS APPROACH; LANDFILL SITE SELECTION; PERFORMANCE EVALUATION; DECISION-MAKING; TOPSIS; SIMULATION; MODEL; Environmental Sciences & Ecology